2018
DOI: 10.1039/c8cy01111g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of amorphous mesoporous manganese oxides for efficient catalytic decomposition of ozone

Abstract: Amorphous mesoporous manganese oxides (MnOx) with different microstructures were synthesized via a facile redox method between manganese acetate and potassium permanganate by modulating the addition sequence of the precursors and directly used for catalytic decomposition of ozone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 60 publications
3
48
0
Order By: Relevance
“…Figure (a) depicts the O 2 ‐TPD curves of the gained catalysts and it can be seen that each curve consists of two different peaks. According to the literature, peaks at temperatures <400 °C are commonly believed to be the desorption of surface‐adsorbed oxygen species (O 2 − and O − ) that are related to the oxygen vacancies in metal oxides, whereas those peaks at temperatures higher than 400 °C can be assigned to the desorption of lattice oxygen species (O 2− ) . As seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure (a) depicts the O 2 ‐TPD curves of the gained catalysts and it can be seen that each curve consists of two different peaks. According to the literature, peaks at temperatures <400 °C are commonly believed to be the desorption of surface‐adsorbed oxygen species (O 2 − and O − ) that are related to the oxygen vacancies in metal oxides, whereas those peaks at temperatures higher than 400 °C can be assigned to the desorption of lattice oxygen species (O 2− ) . As seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…According to the literature, peaks at temperatures <400 ∘ C are commonly believed to be the desorption of surface-adsorbed oxygen species (O 2 − and O − ) that are related to the oxygen vacancies in metal oxides, whereas those peaks at temperatures higher than 400 ∘ C can be assigned to the desorption of lattice oxygen species (O 2− ). 37,38 As seen in Fig. 7(a), both adsorbed oxygen species and lattice oxygen species of Ni-containing catalysts showed lower desorption temperatures than those of MnO x , implying looser bonding of oxygen species to the Mn-Ni composite oxides.…”
Section: Characterizationsmentioning
confidence: 91%
“…The active components of the catalyst mainly include noble metals [13][14][15] and transition metal oxides. [16][17][18][19] Imamura et al reported that p-type semiconductors have higher decomposition efficiency for ozone than n-type semiconductors. 20 Oyama measured the conductivity of the catalyst by the Hall effect and compared the correlation between oxide activity and conductivity, thereby further conrming that the p-type semiconductor oxide has higher activity for the catalytic decomposition of ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MnO 2 have been prepared by reduction of KMnO 4 with MnSO 4 .H 2 O via a hydrothermal method and used for catalytic oxidation of HCHO [26], ozone decomposition [27], etc.…”
Section: Introductionmentioning
confidence: 99%